PENGARUH PENDEKATAN PEMBELAJARAN DAN TINGKAT KEMAMPUAN BERPIKIR KREATIF SISWA TERHADAP HASIL BELAJAR IPA PADA KELAS V SDN-1 MENTENG KOTA PALANGKA RAYA TAHUN AJARAN 2021/ 2022 - Manatap Siringoringo (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The background of this research is the phenomenon that illustrates that teachers are people who are obliged to create a classroom atmosphere so that learning can be successful. Elementary teachers’ role in general is highly dominant in providing information, while students listen and take notes. Many teachers teach science in a less interesting or boring way, do not master the materials taught, and do not provide opportunities for students to actively participate and develop the skills and attitudes of scientists, with science phenomena that exist in the environment around students. The inquiry approach emphasizes concept discovery and encourages students’ confidence that students have the skills required. Students' activities to search for a solution in a problem-solving process, cannot be separated from its characteristics, namely the basic ability of creative thinking. This research will reveal the difference between inquiry learning and expository learning, the difference between high and low creative thinking skills, and the relationship between learning approaches and creative thinking skills on science learning outcomes.